2007
DOI: 10.1681/asn.2006020164
|View full text |Cite
|
Sign up to set email alerts
|

A Sensitized Screen of N-ethyl-N-nitrosourea–Mutagenized Mice Identifies Dominant Mutants Predisposed to Diabetic Nephropathy

Abstract: Diabetic nephropathy (DN) is a late diabetic complication that comprises progressively increasing albuminuria, declining GFR, and increased cardiovascular risk. Only a minority of patients with diabetes (25 to 40%) develop nephropathy, and there is evidence that heritable genetic factors predispose these "at-risk" individuals to DN. Comparing variability among inbred mouse strains with respect to a specific phenotype can model interhuman variability, and each strain represents a genetically homogeneous system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 47 publications
(55 reference statements)
2
12
0
Order By: Relevance
“…Furthermore, as described by others in previous studies, we observed mesangial expansion as sign of early diabetic glomerular alterations by both light and electron microscopic examination. 10,17,32,33 In addition, an increase of urinary albumin excretion was noted, indicative of some abnormality of glomerular permselectivity, but as in other studies in Ins2 ϩ/Ϫ mice, the increase in albumin excretion was mild. 16,17,32,34 Our BASIC RESEARCH www.jasn.org study shows that the glomerular abnormalities observed in Ins2 ϩ/Ϫ mice are enhanced in these mice when they lack A1AR.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Furthermore, as described by others in previous studies, we observed mesangial expansion as sign of early diabetic glomerular alterations by both light and electron microscopic examination. 10,17,32,33 In addition, an increase of urinary albumin excretion was noted, indicative of some abnormality of glomerular permselectivity, but as in other studies in Ins2 ϩ/Ϫ mice, the increase in albumin excretion was mild. 16,17,32,34 Our BASIC RESEARCH www.jasn.org study shows that the glomerular abnormalities observed in Ins2 ϩ/Ϫ mice are enhanced in these mice when they lack A1AR.…”
Section: Discussionsupporting
confidence: 68%
“…In a previous study in Akita mice that did not include comparison with WT controls, GFR was reported to be 520 Ϯ 120 l/min, similar to our value of 457 Ϯ 29 l/min and consistent with mild hyperfiltration. 10 Overall, the degree of hyperfiltration in various diabetic mouse models has been modest and seems to depend on both duration and strain. In this regard, hyperfiltration has been found at 3 mo of age in both OVE26 mice, a type 1 diabetic model, and in db/db mice, a model of type 2 diabetes [11][12][13] ; no hyperfiltration was observed in either strain when mice were older than 5 mo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This new strain is therefore ideal for holistic transcriptome and proteome studies aiming at the identification of molecular mechanisms underlying GH-induced alterations particularly of the kidney. Moreover, genetically defined cba-bGH mice facilitate random mutagenesis screens for modifier genes which influence the effects of chronic GH excess and associated pathological lesions (Rathkolb et al 2005;Tchekneva et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…A dominant suppressor screen in Mecp2-deficient mice (Rett syndrome) identified a mutation in squalene epoxidase (Sqle) as a heritable suppressor, resulting in prolonged survival and amelioration of neurologic manifestations (19). Other successful sensitized screens include analysis of mouse mutants predisposed to diabetic nephropathy (20), a screen in Sox10 haploinsufficient mice identifying the Gli3 gene as a modifier of neurocristopathy Significance Venous thromboembolism (VTE) is a common disease characterized by the formation of inappropriate blood clots. Inheritance of specific genetic variants, such as the Factor V Leiden polymorphism, increases VTE susceptibility.…”
mentioning
confidence: 99%